Outbreak of scombroid fish poisoning, Taiwan. - Chen, K T (1987)
Fish implicated in outbreaks of scombroid poisoning have usually undergone prolonged storage at an inadequate temperature. We report an outbreak of scombroid poisoning in which fish stored on ice for two days caused illness after standing at room temperature for only three to four hours; fish from the same catch did not cause illness after standing at room temperature only one hour. This outbreak suggests scombrotoxins may be produced more rapidly than previously thought possible.